Paroxysmal Nocturnal Hemoglobinuria in the Context of a Myeloproliferative Neoplasm: A Case Report and Review of the Literature - Giannotta, Juri Alessandro; Fattizzo, Bruno; Barcellini, Wilma (Frontiers in Oncology, 2021)
Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by intravascular hemolytic anemia and thrombosis, and is notoriously associated with aplastic anemia and myelodysplastic syndromes. Rarer associations include myeloproliferative neoplasms (MPN), which are also burdened by increased thrombotic tendency. The therapeutic management of this rare combination has not been defined so far. Here we describe a 62-year-old man who developed a highly hemolytic PNH more than 10 years after the diagnosis of MPN. The patient started eculizumab obtaining good control of intravascular hemolysis but without amelioration of transfusion-dependent anemia. Moreover, we performed a review of the literature regarding the clinical and pathogenetic significance of the association of PNH and MPN. The prevalence of PNH clones in MPN patients is about 10%, mostly in association with JAK2V617F-positive myelofibrosis. Thrombotic events were a common clinical presentation (35% of subjects), sometimes refractory to combined treatment with cytoreductive agents, anticoagulants and complement inhibitors. The latter showed only partial effectiveness in controlling hemolytic anemia, and, due to the paucity of data, should be taken in consideration after a careful risk/benefit evaluation in this peculiar setting.